Liberdade e o fundamento do direito e da justiça em Kant - Portilho, Claiton Rui da Costa (2009)
This research aims to present the possibility of a foundation of law and justice from the idea of freedom developed by Kant in the Groundwork of the Metaphysics of Morals and its justification since the conception of good will, through the concept of duty, the concept and formulations of the categorical imperative and his distinction of hypothetical imperatives, autonomy as a practical reason, to freedom as a corollary of the ethic system. Considering the division of moral drawn by Kant in the Metaphysics of Morals in Doctrine of Law and Doctrine of the Virtue, the approach of the metaphysics foundations on the doctrine of law is necessary, since the concepts of state, law, civil society, coercion and primordial contract are, as ideas, derived from the same practical reason that is articulated in moral philosophy and constitute the State of Law, taken in its public meaning, in which freedom has great importance both foundation as autonomy of the citizens in their coexistence in a social and political corps. The rationality and freedom as law s and ethic principles are, still admitting distinctions for Kant, the foundation of such systems, which motivates arguments until today, but whose importance and influence nor the critics deny.